Numerical simulation and experimentation of endodontic file using Taguchi DoE - Lokhande Pravin R. (EDP Sciences, 2021)
The endodontic file is a tapered, needle shape body used for the preparation of curved human root canals. During the preparation, process files get failed due to the locking action offered by the canal wall. The present study aimed to find the fatigue life of endodontic files at 23°, 33° and 43° root canal curvature angles. Four brands of files were selected for the present study viz. Hyplex CM, Pro-Taper Next, Hero Shaper, Pro-File Vortex. The strain life analysis done using ANSYS showed that the Hyplex CM file gives the highest fatigue life at 23°, 33° and 43° root canal curvature angles. Therefore, Hyplex CM file was selected for DoE Taguchi Optimization study. Each experimental reading was conducted on X Smart Plus experimental setup under purely rotary and combined reciprocating-rotary motion, at 500 rpm, 600 rpm and 700 rpm and 23°, 33° and 43° root canal curvature angles. Hyplex CM file given maximum fatigue life at 23° root canal curvature angle and 500 rpm speed of rotation. But if file motion is combined rotary-reciprocating, life reduces. The ANNOVA study showed that P-value and significance F are very small, which represented that the regression model is effective.